2018
DOI: 10.4155/fsoa-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

RAB40C Regulates RACK1 Stability Via the Ubiquitin–Proteasome System

Abstract: Aim:RACK1 is a multifunctional scaffolding protein that is expressed in many cellular compartments, orchestrating a number of signaling processes. RACK1 acts as a signaling hub to localize active enzymes to discrete locations; therefore tight control of RACK1 is vital to cellular homeostasis. Our aim was to identify the mechanisms responsible for RACK1 turnover and show that degradation is directed by the ubiquitin proteasome system.Results:Using siRNA screening, we identified RAB40C as the ubiquitin E3 ligase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
(56 reference statements)
0
19
0
Order By: Relevance
“…S5b ). Previous studies showed that RACK1 may function as a substrate or an E3 ligase itself [ 22 , 23 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5b ). Previous studies showed that RACK1 may function as a substrate or an E3 ligase itself [ 22 , 23 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that lysine selection is essential for the generation of diverse substrate–Ub structures, targeting proteins to different fates [ 37 ]. However, the specific ubiquitination sites of RACK1 remain unclear so far [ 22 ]. Our studies found that the lysine K172, K225, and K257 residues of RACK1 are responsible for UBE2T-mediated RACK1 ubiquitination and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, downregulation of RACK1 protein was evident with PHB2 depletion and was blocked by MG132, which interrupts the ubiquitin-proteasome pathway. Previous studies reported that RACK1 turnover is influenced by the ubiquitin-proteasome system 29 , 30 . As PHB2 binds to RACK1 and positively regulates RACK1 protein stability, we hypothesized that PHB2 increases RACK1 expression by decreasing ubiquitination of RACK1.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, PHB2 decreased degradation of RACK1 in a proteasome-dependent manner, as evidenced by the restrained effect of the proteasome inhibitor MG132 on RACK1 degradation and the decreased RACK1 ubiquitination in PHB2-overexpressing cells. Although Day et al 29 identified RAB40C as a ubiquitin E3 ligase responsible for the ubiquitination of RACK1, other E3 ligases may also be involved in RACK1 ubiquitination, and this issue deserves deeper exploration. All these findings indicate that PHB2 may be involved in the modulation of RACK1 stability and expression via posttranslational modification.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the silencing of the MZB1 gene with methylation described in hepatocellular and gastric cancers could be seen as a form of immunological tolerance [ 36 , 37 ], while MZB1 protein was increased in B-cells from patients with the autoimmune condition systemic lupus erythematosus [38] . Finally, RAB40C protein regulates, via an ubiquitin-proteasome system, the degradation of RACK1 protein, which is important in tumour growth and T-cell migration [39] . The RAB40C gene was also among the main genes silenced with methylation in breast cancer [40] , matching the lower expression in TOL compared to Non-TOL KTRs that we observed.…”
Section: Discussionmentioning
confidence: 99%